Interacción orientada a aspectos en entornos multiorganizacionales - Corchuelo, Rafael; Pérez, José Antonio; Ruiz Cortés, Antonio (Revista Colombiana de Computación, 2002)
Unfortunately, current proposals that focus on separation of concerns assume that objects interact by means of object-oriented method calls, which implies that they embed interactions with others into their functional code. This makes them dependent on this interaction model, and makes it difficult to reuse them in a context in which another interaction model is more suited. Keywords: Aspect orientation, interaction models, multiparty interactions.